ASSOCIATION OF MOTHER ANXIETY AND CHILDREN DENTAL PREVALENCE ON ORAL HEALTH QUALITY OF THEIR CHILDREN - Darmayanti Siregar; Siska Ella Natassa; Lily Sofiani (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Children's oral health is influenced by several factors related to their mother's condition. Mothers who have poor oral health generally have high anxiety about dentists and will rarely visit dental health services so their children will have poor oral health and oral problems will arise, especially caries. This has a negative impact on the quality of life of children. This study aims to determine the effect of maternal dental anxiety and child caries status on the quality of life of school children in an elementary school in Medan City. Methods: A cross-sectional design was conducted with 71 students, 6 until 7 years-old elementary schools in Medan. Maternal dental anxiety was measured using a Dental Anxiety Scale (DAS) questionnaire and children's quality of life was measured using a Parental Perception Questionnaire (PPQ). The child's caries status was assessed by taking with a smartphone camera and calculating the presence or absence of caries in each child. Results: Caries prevalence in children was 29.6%, maternal dental anxiety 88.7% low, 2.8% high anxiety. The mean score of maternal anxiety was 10.04± 3.46 and the child's quality of life score was 22.48±13. There is a significant effect between caries status and oral symptoms (p-value= 0.012) and  functional limitations (p value = 0.039). Conclusion: Mothers who have high anxiety about dental care will ignore visits to the doctor. If there are dental and oral problems such as caries in children, this condition becomes protracted and affects the quality of life of children. Keywords: Caries, Dental anxiety, Maternal, Oral health, Quality of life